5-Alpha-Reductase 2 Deficiency in a Woman with Primary Amenorrhea. (7th December 2013) - Maleki, Nasrollah; Kalantar Hormozi, Mohammadreza; Iranparvar Alamdari, Manouchehr; Tavosi, Zahra
Abstract : Steroid 5-alpha-reductase 2 deficiency is a rare disorder leading to male pseudohermaphroditism, a condition characterized by incomplete differentiation of male genitalia in 46, XY patients. Here, we report a case of a 21-year-old woman from Ardabil who presented with primary amenorrhea, ambiguous genitalia, and lack of breast development. All of the serum hormone profiles were normal except for raised serum total testosterone. Testosterone to DHT ratio (T/DHT) was elevated before (15.72) and further increased after hCG stimulation (32.46). A chromosomal study revealed a 46, XY karyotype. A bilateral gonadectomy, recessive cliteroplasty, urethroplasty, and vaginoplasty were performed and hormonal replacement therapy using estrogen was started. In conclusion, the diagnosis of 5-alpha-reductase 2 deficiency may be suspected in infants with ambiguous genitalia or in adolescents or young adults with the characteristic phenotype and serum hormone profiles.